FEATURES OF FINANCIAL RESOURCE MANAGEMENT OF A UNIVERSAL BANK IN MODERN CONDITIONS - Чупринка, Катерина; Лиса, Олена (SWorldJournal, 2026)
The article addresses the pressing issue of effective management of financial resources in a universal bank under conditions of macroeconomic instability and martial law in Ukraine. The banking system accumulates a significant volume of funds from various